One-step coaxial electrodeposition of Co0.85Se on CoNi2S4 nanotube arrays for flexible solid-state asymmetric supercapacitors - Zhang, Chunyan (2020)
A one-step electrochemical method is applied to coaxially deposit highly conductive Co0.85Se nanosheets composed of ultrasmall Co0.85Se nanocrystals on three-dimensional (3D) CoNi2S4 nanotube arrays supported on graphene foam (GF) (Co0.85Se@ CoNi2S4/GF) as an electrode for flexible solid-state supercapacitors. The Co0.85Se@CoNi2S4/GF electrode has an areal capacitance of 5.25 F cm−2 at 1 mA cm−2 and good rate capability (2.65 F cm−2 at 20 mA cm−2). A solid-state asymmetric supercapacitor with Co0.85Se@NiCo2S4/GF as the cathode and hollow carbon spheres (HCSs) as the anode in a PVA/KOH electrolyte was assembled which shows an energy density of 46.5 W h kg−1 at a power density of 750 W kg−1, and 89.0% capacity retention after 10 000 cycles over a potential window of up to 1.55 V. These results demonstrate that the electrodeposition method is applicable for engineering of 3D microstructured electrodes and also provides an efficient strategy for fabricating transition metal selenide based nanodevices.